John Huston's wise blood [videorecording (DVD)] - Huston, John, 1906-1987; Huston, John, 1906-1987; Dourif, Brad, 1950-; Stanton, Harry Dean, 1926-2017; Beatty, Ned; Prose, Francine, 1947-; O'Connor, Flannery (Criterion collection, 2009)
U.S. Army war veteran Hazel Motes may not be a believing Christian, but he somehow makes observations about the state of a run-down country church and understands that there are ridiculous frauds on the streets. When a cab driver insists he looks like a preacher in his new hat, Hazel takes on the part. He starts his own new Church of Truth, without the crucified Jesus. His first disciple is an 18-year old simpleton with a 'prophetic gift.'